Social Preferences under the Shadow of the Future - Felix Kölle; Simone Quercia; Egon Tripodi (Center for Economic Studies and ifo Institute (CESifo), 2023)
Social interactions predominantly take place under the shadow of the future. Previous literature explains cooperation in indefinitely repeated prisoner's dilemma as predominantly driven by self-interested strategic considerations. This paper provides a causal test of the importance of social preferences for cooperation, varying the composition of interactions to be either homogeneous or heterogeneous in terms of these preferences. Through a series of pre-registered experiments (N = 1,074), we show that groups of prosocial individuals achieve substantially higher levels of cooperation. The cooperation gap between prosocial and selfish groups persists even when the shadow of the future is increased to make cooperation attractive for the selfish and when common knowledge about group composition is removed.
Keywords: C73; C91; C92; 330; cooperation; indefinitely repeated games; prisoner's dilemma; social preferences; experiment